Synthesis of Magnetic Iron Oxide Nanoparticle from Logas Natural Sand and Its Application for the Catalytic Degradation of Methylene Blue. (October 2020) - Septiawan, Rebi; Amiruddin, Erwin; Awaluddin, Amir; Hadianto, Heri; Davini, Nindi
Abstract: Structural properties, morphology, and the catalytic activity of hematite (α-Fe2 O3 ) nanoparticles for degradation of methylene blue have been studied. For this purpose, the hematite particles were synthesised from Logas natural sand by 2 steps ball milling method. X-ray diffraction (XRD) confirmed the presence of a hematite (α-Fe2 O3 ) phase. However, other phases such as SiO2 and FeTiO3 are also confirmed by XRD. Scanning electron microscopy (SEM) showed a wide distribution of particle sizes. Moreover, the shape of the grains is irregular form. The effect of reaction time and hematite nanoparticles dosage which affect the efficiency of catalytic reaction was investigated. Catalytic activity of hematite nanoparticles in the degradation of methylene blue (MB) was studied through ultraviolet visible spectroscopy (UV-Vis).